Genes predisposing to type 1 diabetes mellitus and pathophysiology: a narrative review (Faculty of Medicine Universitas Indonesia, 2020)
The possibility of targeting the causal genes along with the mechanisms of pathogenically complex diseases has led to numerous studies on the genetic etiology of some diseases. In particular, studies have added more genes to the list of type 1 diabetes mellitus (T1DM) suspect genes, necessitating an update for the interest of all stakeholders. Therefore this review articulates T1DM suspect genes and their pathophysiology. Notable electronic databases, including Medline, Scopus, PubMed, and Google-Scholar were searched for relevant information. The search identified over 73 genes suspected in the pathogenesis of T1DM, with human leukocyte antigen, insulin gene, and cytotoxic T lymphocyte-associated antigen 4 accounting for most of the cases. Mutations in these genes, along with environmental factors, may produce a defective immune response in the pancreas, resulting in β-cell autoimmunity, insulin deficiency, and hyperglycemia. The mechanisms leading to these cellular reactions are gene-specific and, if targeted in diabetic individuals, may lead to improved treatment. Medical practitioners are advised to formulate treatment procedures that target these genes in patients with T1DM.